A panchromatic spatially resolved study of the inner 500 pc of NGC 1052. Issue Volume 15:Issue S359(2020) (March 2019) - Dahmer-Hahn, Luis G.; Riffel, Rogério; Ricci, Tiago V.; Steiner, João E.; Storchi-Bergmann, Thaisa; Riffel, Rogemar A.; Menezes, Roberto B.; Dametto, Natacha Z.; Diniz, Marlon R.; Motter, Juliana C.; Ruschel-Dutra, Daniel
Abstract: We analyzed the inner 320 × 535 pc 2 of the elliptical galaxy NGC 1052 with integral field spectroscopy, both in the optical and in the near-infrared (NIR). The stellar population analysis revealed a dominance of old stellar populations from the optical data, and an intermediate-age ring from NIR data. When combining optical+NIR data, optical results were favoured. The emission-line analysis revealed five kinematic components, where two of them are unresolved and probably associated with the active galactic nucleus (AGN), one is associated with large-scale shocks, one with the radio jets, and the last could be explained by either a bipolar outflow, rotation in an eccentric disc or a combination of a disc and large-scale gas bubbles. Our results also indicate that the emission within the galaxy is caused by a combination of shocks and photoionization by the AGN.